Implementation Prospects of Investment Process For The Investors - ugli , Murtazaev (American Journal of Economics and Business Management, 2024)
The article covers the formation and development of the accumulative pension fund, its influence on the development of capital investment in production activities. Specific factors that can narrow the fund’s participation in investment projects are given. Specific proposals are given to activate the investment of the fund’s capital in the company’s activities. This study explores the development and challenges of institutional investment processes in Uzbekistan, focusing on the accumulative pension fund (APF) as a key player in the country’s investment landscape. Utilizing both quantitative and qualitative research methodologies, data from official Uzbek databases were analyzed statistically. The results highlight significant limitations in the current investment climate, including underdeveloped financial infrastructure, narrow investment portfolios, and regulatory constraints on fund activities. Despite these challenges, the APF has the potential to catalyze market growth through strategic investments in securities and corporate bonds. The study concludes that creating a favorable investment environment, coupled with improved management practices and broader financial instruments, could transform institutional investors into vital contributors to Uzbekistan’s economic growth and industrial development